PRODI STUDI AGAMA-AGAMA SEBAGAI PELOPOR INKLUSIFITAS BERAGAMA: REFLEKSI PENGALAMAN PRODI STUDI AGAMA-AGAMA UIN ALAUDDIN MAKASSAR - Indo Santalia; Syamsul Arif Galib (Religi: Jurnal Studi Agama-agama, 2019)
Radicalism is a complex problem. By that, a holistic approach is needed to overcome this issue. Every element of society and the state are morally responsible to support the process of deradicalization and strengthening the spirit of togetherness as a nation. This paper tries to explain how Religious Studies can be a study program that is expected to be able to support and  actively involved in preventing young people engage with radicalism. All this time, radicalism has been understood to arise because of exclusives religious attitudes. On the contrary, religious studies is a place that leads students to get out of the trap of religious exclusivity. Religious Studies is an incubator where  the spirit of religious inclusiveness is built. The attempts to counter radicalism can be one of the works for religious studies majors, especially the Religious Studies of Alauddin State Islamic University, Makassar. The religious study program must be at the forefront of campaigning religious inclusivity, anti-religious radicalism and also initiating a spirit of tolerance between religions.